PENERAPAN HUKUM DALAM PERTIMBANGAN HAKIM UNTUK MENJATUHKAN PUTUSAN PIDANA TERKAIT HAL YANG MEMBERATKAN DAN MERINGANKAN DI PENGADILAN NEGERI SIGLI - Ridha Nur Arifa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
Considerations regarding aggravating and mitigating factors in the verdict are regulated in Article 197 letter d and 197 letter f of the Criminal Procedure Code), however, there are several judges' decisions at the Sigli District Court that are only based on aggravating or mitigating factors. This paper aims to examine the judge's considerations in handing down decisions regarding aggravating and mitigating factors and the impact of the judge's considerations regarding aggravating and mitigating factors on the perpetrator. The research method used in this study is an empirical juridical research method, namely by looking at the implementation or implementation of normative legal provisions in action in every specific legal event that occurs in society. Based on the results of the study, it shows that the judge's considerations in handing down sentences related to aggravating and mitigating factors include juridical and non-juridical considerations. The impact of the judge's considerations regarding aggravating and mitigating factors on the perpetrator is in terms of aggravating so that with the intention of providing a lesson so that in the future the defendant will not commit his actions again and also so that in the future the defendant can realize and be aware of the crimes or actions that have been committed. The impact of mitigating the sentence imposed by a judge is solely to educate, guide, and foster the defendant so that after serving his sentence, the defendant can return to society and be accepted. A judge's decision in accordance with the law has a positive impact on various aspects, including legal certainty, justice, and benefits for society.